Grafting Cucumber Onto Pumpkin Induced Early Stomatal Closure by Increasing ABA Sensitivity Under Salinity Conditions - Niu, Mengliang; Sun, Shitao; Nawaz, Muhammad Azher; Sun, Jingyu; Cao, Haishun; Lu, Junyang; Huang, Yuan; Bie, Zhilong (Frontiers in Plant Science, 2019)
In the early period under salt stress conditions, reduced stomatal opening could prevent water loss and avoid wilting. ABA signal plays an important role during this process. Here, we show that cucumber grafted onto pumpkin have a more rapid stomatal closure that helps plant adapt to osmotic stress caused by salinity. Accelerated abscisic acid (ABA) contents in the root, xylem sap and leaf were evaluated for the two grafting combinations (self-grafted cucumber and cucumber grafted onto pumpkin rootstock), and four transcript of ABA signaling genes (NCED2, ABCG22, PP2C and SnRK2,1) were also investigated. Results showed that root-sourced ABA signal lead to a decreased stomatal opening and transpiration in the plants grafted onto pumpkin compared with plants grafted onto cucumber. Furthermore, plants grafted onto pumpkin had an increased sensitivity to ABA compared with self-grafted cucumbers. Inhibition of ABA biosynthesis with fluridon in roots increased the transpiration rate (Tr) and stomatal conductance (Gs) in the leaves. Our study demonstrated that the roots of pumpkin have developed an enhanced ability and make the scion more sensitive to ABA that is delivered from root to shoot and enhances osmotic tolerance under NaCl stress. Such a mechanism can be greatly exploited to benefit the vegetable production particularly in semiarid saline regions.